GAMBARAN DUKUNGAN KELUARGA PADA ANAK USIA SEKOLAH DASAR DI DESA GUMIWANG KECAMATAN WURYANTORO - Nurtanti, Susana (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
The background of this research is the importance of family support for elementary school age children because with family support the children can control their behavior. Of the 200 abandoned children studied in Surabaya, it was found that only 3.5% of respondents admitted that their parents or their families had never been mistreated. Almost all neglected children admit to having been the object of violence in the family (96.5%), and even 61% of them admit to being treated harshly. Of the 200 abandoned children, 70% admitted that they were often victims of beatings at home, 66% admitted that they were abused. The purpose of this study was to determine family support for elementary school aged children. The design of this research is descriptive, the number of samples is 50 respondents with purposive sampling technique. The results showed family support for elementary school age children in Gumiwang Village, Wuryantoro District, indicated by the results of statistical data processing that the frequency distribution of family support with a good score was 35 (70.0%), while the frequency distribution of family support with a bad score was 15 (30.0%).